The Relationship between the Adherence Level of the use of Scientific Herbal Medicine and Its Success in Hypertension Therapy - Anggita Rahmawati; Truly Anggraini; Novena Yety Lindawati (Indonesian Journal of Global Health Research, 2024)
Hypertension has the most significant prevalence among non-communicable diseases (NCDs) in Indonesia. The prevalence of hypertension in 2018 of 34.11% rose 8.31% from the prevalence of hypertension in 2013 of 25.8%. Data from the Ministry of Health of the Republic of Indonesia indicates that 32.3% of hypertension patients exhibit non-compliance or do not regularly adhere to medication regimens, thereby increasing their mortality risk. The objective of this study was to establish the magnitude of the impact caused by the compliance level to the use of antihypertensive scientific herbal medicines on the effectiveness of hypertensive patients’ therapy in UPF. Yankestrad Rs Dr. Sardjito Tawangmangu. This study descriptively utilized a quantitative cross-sectional method using the MARS-5 (Medication Adherence Report Scale) questionnaire to measure adherence level. The sample of this study consisted of 150 purposively hypertensive respondents out of the total sample size of the 150 who conducted the research in October 2023. Data analysis includes univariate and bivariate analysis with a chi-square test. The research findings provide a reliable understanding of compliance levels. A very low compliance level was recorded at 32 or 21.3%, a moderate compliance level was recorded at 53 or 35.3% and a high compliance level was recorded at 65 or 43.4%. The chi-square supported the association thus out of 113 respondents the p-value at 0.001 and where the relationship can be a very healthy therapy at UPF Yankestrad Dr. Sardjito Tawangmangu Hospital.